Traumatizing Aspects of Providing Counselling in Community Agencies to Survivors of Sexual Violence: A Concept Map - Kadambi, Michaela A.; Truscott, Derek (Canadian Journal of Counselling and Psychotherapy, 2008)
Concept mapping (a combined qualitative/quantitative approach) was used to clarify and understand 72 Canadian professionals’ experience of what they found to be traumatizing about their work with sexual violence survivors in community settings. A sample of 30 professionals providing community-based treatment to survivors of sexual violence sorted and rated 96 individual statements (generated by 72 professionals) regarding the traumatizing aspects of this clinical work to produce a visual representation, or concept map, of their experience. The final concept map generated eight distinct cluster themes: Witnessing and Responding to Therapeutic Content, Witnessing and Responding to Therapeutic Process, Challenging Countertransference Reactions, System Flaws and Inadequacies, Societal Injustice, Awareness of Human Cruelty, Feeling Helpless and Powerless, and Workplace Constraints and Deficiencies. The implications of these findings and suggestions for further areas of investigation are discussed.